Literary challenges to the heroic myth of the Voortrekkers : H.P. Lamont's War, wine and women and Stuart Cloete's Turning wheels - Hale, Frederick (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2001.